واقع النظام الميزانياتي في ظل توجه الجزائر نحو تطبيق معايير المحاسبة الدولية للقطاع العام. IPSAS دراسة حالة مديرية الشباب والرياضة لوالية الوادي - جار الله،مصباح; بوطي،عبد الفتاح; واده،طه; بقيطة،منار (university of eloued جامعة الوادي, 2024)
تهدف هذه الدراسة الى تسليط الضوء على أهمية تبني معايير المحاسبة الدولية للقطاع العام وإلى توضيح متطلبات إصالح نظام المحاسبة العمومية في الجزائر، من خالل استعراض الدراسات السابقة ومن خالل اإلصالحات التي باشرتها الدولة لتحديث النظام الميزانياتي. وخلصت الدراسة إلى أن النظام الحالي للمحاسبة العمومية في الجزائر ال يلبي احتياجات المستخدمين، وهناك توجه نحو إصالح هذا النظام من خالل مشروع المخطط المحاسبي للدولة، إن تبني معايير المحاسبة الدولية للقطاع العام في البيئة الجزائرية يسهم في تطوير نظام المحاسبة العمومية من خالل تحسين الشفافية والمساءلة وجودة التقارير المالية والموثوقية والفعالية في المعلومات المالية العامة، وكذلك القضاء على الفساد اإلداري، وبالتالي يمكن القول إن الجزائر تتجه نحو تطبيق إصالح النظام المحاسبي في القطاع العام لمواءمته مع المعايير الدولية وتعزيز ممارسات اإلدارة المالية، باإلضافة إلى ذلك يستكشف البحث تأثير تطبيق معايير الحاسبة الدولية للقطاع العام على جودة المعلومات المالية وكفاءة القطاع العام بشكل عام في الجزائر This study aims to shed light on the importance of adopting International Public Sector Accounting Standards (IPSAS) and to clarify the requirements for reforming the public accounting system in Algeria. This is achieved through reviewing previous studies and the reforms initiated by the state to modernize the budgetary system. The study concluded that the current public accounting system in Algeria does not meet the users' needs, and there is a trend towards reforming this system through the state's accounting plan project. Adopting IPSAS in the Algerian environment contributes to developing the public accounting system by improving transparency, accountability, the quality of financial reports, reliability, and effectiveness in public financial information, as well as combating administrative corruption. Therefore, it can be said that Algeria is moving towards implementing a reform of the public sector accounting system to align it with international standards and enhance financial management practices. Additionally, the research explores the impact of implementing IPSAS on the quality of financial information and the overall efficiency of the public sector in Algeria.
مذكرة ماستر محاسبة
Keywords: International Public Sector Accounting Standards; Public accounting; Budget reform.; معايير المحاسبة الدولية للقطاع العام، المحاسبة العمومية، اإلصالح الميزانياتي.